Avoiding Flood by Improving Cross-Sectional Capacity through River Normalization - Harits, Muzhaffar; Sapei, Asep; Pandjaitan, Nora Herdiana (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Bekasi is one of the regions in Indonesia that often suffer from flooding. To overcome flooding problems in the Bekasi area, the Ciliwung Cisadane River Basin Center has begun a normalization project along the Bekasi River. This research aimed to evaluate the Bekasi River's cross-sectional capacity both before and after normalization. The analysis focused on the section where the Cileungsi and Cikeas rivers converge to the Bekasi weir. In this research, secondary data were employed, such as national digital elevation model data, detailed engineering designs of Bekasi River flood control activities, and rainfall data from the Cibinong Station that covers the period from 2006 to 2020. The result from planned flood discharge with the Nakayasu synthetic unit hydrograph method for a return period of 25 years on the Bekasi River was obtained at 665.81 m3/s. The results of hydraulic analysis before normalization with the HEC-RAS application show that flooding occurred at 102 out of 116 stations, with capacities of river cross-sections ranging from 453.49 m³/s to 665.71 m³/s at these overflow stations. Following the river normalization process, the cross-sectional capacity at all Bekasi River stations can accommodate flood discharge without any instances of overflow.Keywords: Flood, HEC-RAS, Nakayasu, Normalization, Rainfall.